Saint-Petersburg Model of Ethic and Legal Education of Children and Youth: Some Approaches to Process of Formation of Legal Culture of the Personality - Alexey Aleksandrovich Demidov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In this article the authors considered one of the most urgent problems of modern society - the ethical-legal and civil-patriotic education and upbringing of children and youth. Identified regulatory and legal documents in recent years devoted to this issue. For example, the St. Petersburg model of ethical and legal education of children and young people described the formation of the legal culture of the younger generation. The measures, in which the model is, translated Petersburg. We describe some of the ways of development of ethical and legal education.